Indian and Chinese Steel Industry - Gupta, Prateek (2008)
This paper investigates economic impact of the steel industry on the Indian and Chinese economies as these economies are completely different from each other. China is manufacturing intensive, known as factory of the world and India is rich with intellectual property. With the economic impacts, this research investigates the various problems faced by the two economies in their path to become a fully developed economy and the various policies of the two nations to overcome these. The literature review describes the Indian steel industry and factors affecting its growth.